CIRCLE MAPPINGS WITH BREAKS - Karshiboev , Khayrullo Kilichovich (Innovative Development in Educational Activities, 2023)
In this article, we study a one-parameter family of circle homeomorphisms with one break point. It is proved that in the case of a rational rotation number the number of periodic trajectories does not exceed two.